Textual coherence in the Quran Surah Al-Rahman and Al-Waqi'ah as examples (Journal of the College of Basic Education, 2024)
It goes without saying that textual coherence, as a term, emerged in the West, yet it has its roots in our linguistic, literary, and grammatical heritage. However, it appeared under different names, including poetry and prose, among others. Moreover, the difference lies in the fact that the West considered this theory as an independent linguistic textual product in the study of linguistic texts, whereas Arabs did not have such autonomy but rather it was part of other sciences and terminologies. This coherence is clearly manifested in the Quran, especially in Surah Al-Rahman and Al-Waqi'ah, due to the linguistic richness and cohesive semantics found in these two chapters. This is evidenced by repetition (repetition of conjunctions, pronouns, words, and phrases), coherence, and parallelism, aiming to emphasize and validate the meaning, achieving semantic, aesthetic, and rhythmic dimensions. The choice of the Quran for this study is due to its miraculous nature of language and precision of style. Furthermore, the study on the term "textual coherence" was chosen because it is the axis of textual studies, forming the basis for understanding the relationship between words and their context, as well as the relationship between sentences and other sentences, thus leading to the construction of an integrated text with close cohesion.